OVERVIEW OF THE COMPLIANCE OF DIABETES MELLITUS PATIENTS IN UNDERGOING INSULIN THERAPY IN THE WORK AREA OF THE HEALTH CENTER TELING MANADO (STIKES Telogorejo Semarang, 2024)
Background Diabetes Mellitus is currently a disease whose prevalence is increasing. Diabetes mellitus mostly comes from developing countries, one of which is Indonesia. India ranks fifth in the number of people with diabetes mellitus after China, India, Pakistan and the United States. The increasing prevalence of diabetes mellitus can be reduced by complying and continuing throughout his life. The low level of adherence in DM patients, especially regarding consumption of diabetes drugs can have an impact on the risk of complications. Insufficient use of insulin in diabetics is known that some patients stop using insulin because they do not want to provide recovery every day, find it difficult, uncomfortable, and burdensome, are not satisfied with insulin treatment as a whole. The purpose of this study is to know the description of adherence Diabetes Mellitus Patients Undergoing Insulin Therapy in the Working Area of the Teling Manado Health Center. The method used is quantitative descriptive research. Sampling using purposive sampling with a total of 74 samples. The results of the research show that the majority level of adherence is low by 53 (71.6%), and the level of compliance is moderate by 21 (28.4%). The conclusion in this study is that the level of adherence of patients with diabetes mellitus in undergoing insulin therapy is still low, so it is necessary to provide education to patients with diabetes mellitus.